The climate penalty for clean fossil fuel combustion - W. Junkermann; B. Vogel; M. A. Sutton (Atmospheric Chemistry and Physics, 2011)
To cope with the world's growing demand for energy, a large number of coal-fired power plants are currently in operation or under construction. To prevent environmental damage from acidic sulphur and particulate emissions, many such installations are equipped with flue gas cleaning technology that reduces the emitted amounts of sulphur dioxide (SO2) and nitrogen dioxide (NO2). However, the consequences of this technology for aerosol emissions, and in particular the regional scale impact on cloud microphysics, have not been studied until now. We performed airborne investigations to measure aerosol size distributions in the air masses downwind of coal-fired power installations. We show how the current generation of clean technology reduces the emission of sulphur and fine particulate matter, but leads to an unanticipated increase in the direct emission of ultrafine particles (1–10 nm median diameter) which are highly effective precursors of cloud condensation nuclei (CCN). Our analysis shows how these additional ultrafine particles probably modify cloud microphysics, as well as precipitation intensity and distribution on a regional scale downwind of emission sources. Effectively, the number of small water droplets might be increased, thus reducing the water available for large droplets and rain formation. The possible corresponding changes in the precipitation budget with a shift from more frequent steady rain to occasionally more vigorous rain events, or even a significant regional reduction of annual precipitation, introduce an unanticipated risk for regional climate and agricultural production, especially in semi-arid climate zones.